Association of a SIRT1 polymorphism with changes of gray matter volume in patients with first-episode medication-naïve major depression. (30th July 2020) - Nan, Dai; Yuqi, Cheng; Zonglin, Shen; Chenglong, Dong; Na, Li; Fang, Liu; Cong, Zhou; Xiufeng, Xu
Highlights: rs12415800 of the silent mating type information regulation 2 homolog 1 gene (SIRT1 is a promising candidate genetic locus for depression. 166 cases with first-episode medication-naïve major depression and 166 sex and age matched healthy controls were collected to explore the impact of rs12415800 genotypes on gray matter volumes among different brain regions. the risk allele A of rs12415800 (GA/AA) may be associated gray matter volume deficits in right frontal superior, right precuneus, and left precuneus/cuneus only in patients with MDD, not in controls. Abstract: A single nucleotide polymorphism (SNP) rs12415800 of the silent mating type information regulation 2 homolog 1 gene (SIRT1) has shown a genome-wide significant association with major depression disorder (MDD) in a recent GWAS using a large sample. Subsequent studies of SIRT1's biological functions were supportive of a possible role in the pathophysiology of MDD. However, SIRT1-mediated physiopathology of MDD may be brain region specific. In the present study, we investigated the impact of SIRT1 rs12415800 genotypes on gray matter volumes (GMV) among different brain regions in both MDD patients and healthy controls. The rs12415800 was genotyped in 170 patients with first-episode medication-naïve MDD (cases) and 170 healthy controls. Magnetic resonance imaging was conducted and the voxel-based morphometry (VBM) approach was employed to analyze obtained images. When compared with the cases carrying GG genotype, the cases carrying GA or AA genotypes (A for risk allele) showed decreased GMV in right precuneus, left cuneus/precuneus, and right frontal superior. In contrast, the rs12415800-associated GMV abnormalities were not observed in controls. The SIRT1-rs12415800 polymorphism may be associated with the changes of GMV in MDD patients.